-15=-6+4(h+9)

Simple and best practice solution for -15=-6+4(h+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -15=-6+4(h+9) equation:



-15=-6+4(h+9)
We move all terms to the left:
-15-(-6+4(h+9))=0
We calculate terms in parentheses: -(-6+4(h+9)), so:
-6+4(h+9)
determiningTheFunctionDomain 4(h+9)-6
We multiply parentheses
4h+36-6
We add all the numbers together, and all the variables
4h+30
Back to the equation:
-(4h+30)
We get rid of parentheses
-4h-30-15=0
We add all the numbers together, and all the variables
-4h-45=0
We move all terms containing h to the left, all other terms to the right
-4h=45
h=45/-4
h=-11+1/4

See similar equations:

| X-22x+42x-2=180 | | 24/5x=-11/4 | | 3x-5=4x-11 | | 40-9x=131 | | -x-46=4x | | -i-40=9i | | X-56=9x | | b/3-11=-6 | | q=-q | | -2d+9=21 | | t=70-11•3. | | v=23+8,4 | | 5x-35=2x-8 | | 98=t-19 | | 14+2m=4m-12 | | -4(2x-8)=12x | | 48+y=99 | | 0=-0.8x^2+10x+2 | | -2(2s-5)-10=-2(5s+4)-3 | | .5p+2=11 | | x*4,65353=0,09184 | | 2x+1/2x+2(1+x)=90 | | (x/100)*45=7.5 | | (17b-2)-8(2b+2)=-5 | | 61=-19+10a | | w-31-29=-28 | | 3(3w+4)/4=-4 | | -5(2t+7)=55 | | 1.7=-0.7x+0.3 | | -1(2x+8)=-20 | | 4.3n-1.6=2.3n+5 | | 15y^2-45y-50=0 |

Equations solver categories